Study on the mechanism of mining-induced pressure mitigation in gangue backfill mining and the sensitivity analysis of main controlling factors - Zhu, Lei; Xu, Yunong; Liu, Chengyong; Zhou, Yuejin; Gu, Wenzhe; Zhu, Cunli; Liu, Zhicheng (PloS one, 2025)
Gangue backfill mining technology represents a significant advancement in green mining, mitigating mine pressure and rock mass movements, thereby ensuring underground production safety. To investigate the mechanism of pressure reduction and the sensitivity of factors in gangue backfill mining, a mechanical model was first developed. Then, a method for calculating mining pressure in gangue backfill mining was derived based on the stress characteristics. Numerical simulation methods were then employed to analyze the patterns of mining pressure reduction. Finally, sensitivity analysis was performed using range analysis and variance analysis to determine the sensitivity of factors. The results indicate that: (1) The manifestation of mining pressure in gangue backfill mining is influenced by factors such as mining height and backfill collapse ratio; (2) Under the support of coal gangue, the concentrated stress in the coal seam significantly decreases, forming an arched shape according to the mining stages; (3) The range of plastic failure in the coal seam remains relatively stable under gangue backfill mining, with the plastic zone of the roof plate exhibiting a strip-like distribution; (4) Both range analysis and variance analysis revealed that the sensitivity ranking is backfill collapse ratio > mining height > elastic modulus. Variance analysis further confirms that mining height and backfill collapse ratio have significant impacts, while the elastic modulus of coal gangue has a negligible impact. The study analyzed the manifestation law of coal seam pressure under backfill mining and revealed the sensitivity of the main control factors, which can provide theoretical support for the stability control of coal seams under backfill mining.